Direct Reprogramming of Fibroblasts via a Chemically Induced XEN-like State - Li, Xiang; Liu, Defang; Ma, Yantao; Du, Xiaomin; Jing, Junzhan; Wang, Lipeng; Xie, Bingqing; Sun, Da; Sun, Shaoqiang; Jin, Xueqin; Zhang, Xu; Zhao, Ting; et al. (Cell stem cell, 2017)
Direct lineage reprogramming, including with small molecules, has emerged as a promising approach for generating desired cell types. We recently found that during chemical induction of induced pluripotent stem cells (iPSCs) from mouse fibroblasts, cells pass through an extra-embryonic endoderm (XEN)-like state. Here, we show that these chemically induced XEN-like cells can also be induced to directly reprogram into functional neurons, bypassing the pluripotent state. The induced neurons possess neuron-specific expression profiles, form functional synapses in culture, and further mature after transplantation into the adult mouse brain. Using similar principles, we were also able to induce hepatocyte-like cells from the XEN-like cells. Cells in the induced XEN-like state were readily expandable over at least 20 passages and retained genome stability and lineage specification potential. Our study therefore establishes a multifunctional route for chemical lineage reprogramming and may provide a platform for generating a diverse range of cell types via application of this expandable XEN-like state.